The Murdered father in Colombia —Between the manly and the loving father - Orozco, Wilson (Íkala, Revista de Lenguaje y Cultura, 2018)
The present article analyzes the presence of the murdered father in three texts published over the last two decades in Colombia. The texts were chosen for their testi-monial and literary characteristics, the centrality of the father’s death to each of them, and the media impact of all three killings. In each text —Mauricio Aranguren’s Mi confesión, Álvaro Uribe Velez’s No hay causa perdida and Hector Abad Faciolince’s El olvido que seremos— the image of the father is described in depth, and his death presented as a tragic event to which the son then responds. Similarities between the three fathers and the way their sons respond to their deaths are described. Three kinds of reaction are identified: bloody revenge in Mi confesión; saving the nation in No hay causa perdida, and disenchantment in El olvido que seremos